Uma discussão sobre a política de indexação para a Biblioteca Setorial da UFPA Profº. Dr. Francisco Gemaque Álvaro - RAMOS, Carolina Leão (2021)
It consists of a study about the indexing process in the thematic treatment of the information, more specifically on the elements that can compose an indexation policy, whose research problem thought from the absence of an indexation policy officially formalized in the Library of the College of Dentistry of UFPA, which raised in the following question: is it possible to identify elements of indexation policy even if there is not exist a indexing policy manual in the institution? It has as general objective to discuss the elements of indexation policy from the indexing process of the Library of the College of Dentistry, which motivated the development of two specific objectives, a) Search the literature on indexing procedures, indexing policy and its elements; and b) Investigate the possible elements of indexation policy present during the indexing process in the Library of the College of Dentistry of UFPA. Thus, assumes the research as a qualitative exploratory character, through a case study and for the data collection was used the questionnaire as an instrument. It resulted in the presence of 16 elements (indicated and identified) of the 17 that were used as reference, and among them, some deserve to be highlighted because they require more specific reflections, based on what the literature presents, elements identified and indicated as presentation: indexer (training); completeness; correction; and 1 element that was neither indicated nor identified as present: the evaluation of the recovery by subject. It thus considers the characterization of a policy, which allows to infer that because the institution provides guidelines for the performance of the subject indexing activity, understood as conduct, has an indexation policy. This finding does not invalidate the need to elaborate and implement an index policy manual.